Stress related neuropeptides and addictive behaviors: Beyond the usual suspects - Schank, Jesse R. (2012)
Addictive disorders are chronic, relapsing conditions that cause extensive disease burden. Genetic factors partly account for susceptibility to addiction, but environmental factors such as stressful experiences and prolonged exposure of the brain to addictive drugs promote its development. Progression to addiction involves neuroadaptations within neurocircuitry that mediates stress responses, and is influenced by several peptidergic neuromodulators. While corticotropin releasing factor is the prototypic member of this class, recent work has identified several additional stress-related neuropeptides that play an important role in regulation of drug intake and relapse, including the urocortins, nociceptin, substance P and neuropeptide S. Here, we review this emerging literature, discussing to what extent the properties of these neuromodulators are shared or distinct and considering their potential as drug targets.